A differentiation checkpoint limits hematopoietic stem cell self-renewal in response to DNA damage - Wang, Jianwei; Hofmann, Wolf-Karsten (Cell, 2012)
Summary: Checkpoints that limit stem cell self-renewal in response to DNA damage can contribute to cancer protection but may also promote tissue aging. Molecular components that control stem cell responses to DNA damage remain to be delineated. Using in vivo RNAi screens, we identified basic leucine zipper transcription factor, ATF-like (BATF) as a major component limiting self-renewal of hematopoietic stem cells (HSCs) in response to telomere dysfunction and γ-irradiation. DNA damage induces BATF in a G-CSF/STAT3-dependent manner resulting in lymphoid differentiation of HSCs. BATF deletion improves HSC self-renewal and function in response to γ-irradiation or telomere shortening but results in accumulation of DNA damage in HSCs. Analysis of bone marrow from patients with myelodysplastic syndrome supports the conclusion that DNA damage-dependent induction of BATF is conserved in human HSCs. Together, these results provide experimental evidence that a BATF-dependent differentiation checkpoint limits self-renewal of HSCs in response to DNA damage.